Everything is connected art and conspiracy - Eklund, Douglas; Alteveer, Ian; Brown, Meredith A.; Miller, John 1954-; Olmsted, Kathryn S.; Saunders, Beth (The Metropolitan Museum of Art, 2018)
"For the last fifty years, artists have explored the hidden operations of power and the symbiotic suspicion between the government and its citizens that haunts Western democracies. Everything Is Connected: Art and Conspiracy will be the first major exhibition to tackle this perennially provocative topic. It will trace the simultaneous development of two kinds of art about conspiracy. The first half of the exhibition will comprise works by artists who hew strictly to the public record, uncovering hidden webs of deceit--from the shell corporations used by New York's largest private landlord, interconnected networks encompassing politicians, businessmen, and arms dealers. In the second part, other artists will dive headlong into the fever dreams of the disaffected, creating fantastical works that nevertheless uncover uncomfortable truths in an age of information overload and weakened trust in institutions. Featuring seventy works by thirty artists in media ranging from painting and sculpture to photography, video, and installation art, from 1969 to 2016, Everything Is Connected: Art and Conspiracy will present an alternate history of postwar and contemporary art that is also an archaeology of our troubled times." -- Metropolitan Museum of Art website
Published in conjunction with "Everything is Connected: Art and Conspiracy" on view at The Metropolitan Museum of Art, New York, from September 18, 2018, through January 6, 2019
Keywords: Geschichte 1900-; Kunst; Verschwörung -- Motiv; Kunstpolitik; Politics in art / Exhibitions; Conspiracy / In art / Exhibitions; Politics in art; Exhibition catalogs; Ausstellungskatalog -- Metropolitan Museum of Art -- 18.09.2018-06.01.2019 -- New York, NY; Aufsatzsammlung